2020
DOI: 10.3390/f11030274
|View full text |Cite
|
Sign up to set email alerts
|

Do Fire Regime Attributes Affect Soil Biochemical Properties in the Same Way under Different Environmental Conditions?

Abstract: Global change is altering fire frequency and severity in many regions across the world. In this work, we studied the impact of different frequency and severity regimes on the soil biochemical properties in burned areas with different environmental conditions. We selected three sites dominated by pine ecosystems along a Mediterranean-Transition-Oceanic climatic gradient, where we determined the fire frequency, and severity of the last wildfire. Four years after the last wildfire, we established 184 4 m 2 plots.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Soil biochemical properties showed no resistance after wildfire [99], decreasing with burn severity in all the ecosystems. Many authors found a decrease in enzymatic activity immediately after fire [2,88,[100][101][102], as well as a decrease in the activity of these extracellular enzymes with fire burn severity [30,31,46,64] due to the thermal denaturation of soil enzymes [2,66], which occurs above 60-70 • C [44]. The increase in soil pH has also been related to the decrease in β-glucosidase [103] and acid phosphatase [104] activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil biochemical properties showed no resistance after wildfire [99], decreasing with burn severity in all the ecosystems. Many authors found a decrease in enzymatic activity immediately after fire [2,88,[100][101][102], as well as a decrease in the activity of these extracellular enzymes with fire burn severity [30,31,46,64] due to the thermal denaturation of soil enzymes [2,66], which occurs above 60-70 • C [44]. The increase in soil pH has also been related to the decrease in β-glucosidase [103] and acid phosphatase [104] activities.…”
Section: Discussionmentioning
confidence: 99%
“…All these effects mainly occur in the first few centimetres of the surface horizon [2,26,43]. Nutrient cycles are influenced by soil enzymes [44,45], with βglucosidase, urease, and acid phosphatase being among the main enzymatic activities related to the C, N, and P cycles, respectively [2,46]. Enzymes in soils, which catalyse biological reactions [44], are of animal, plant, and microbial sources [45,47].…”
Section: Introductionmentioning
confidence: 99%
“…An exception was C fung in P soils, which significantly increased after the fire, suggesting that the fire favored fungi as compared to bacteria [ 10 ]. Instead, the different behaviors of HA, extracellular enzymes, and DHA, and the intracellular enzymes between unburnt and burnt soils, suggest deep changes in different functional groups of microorganisms [ 53 ]. It can be supposed that after the fire, soil conditions are more disturbed, especially in H soils, as a conspicuous increase in BR and qCO 2 occurred [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe stand-replacing wildfires in Mediterranean fire-prone landscapes might involve substantial impacts on individual soil functions (e.g. Borgogni et al 2019;Fernández-García et al 2020;Huerta et al 2020) and plant community-level properties (e.g. Fernández-Guisuraga et al 2019;Etchells et al 2020), but also on ecosystem multifunctionality (Lucas-Borja et al 2021).…”
Section: Discussionmentioning
confidence: 99%